Proceso de atención de enfermería a paciente masculino de 1 año de edad con DX de síndrome estafilocócico de la piel escaldada. - López Aroca, María Andreina (2023)
Staphyloderma or scalded skin syndrome is defined as an acute epidermolysis caused by a staphylococcal toxin, in which infants and children under 6 years of age are more likely to get it. The lesion at the beginning is usually superficial and crusty. In the next 24 hours, the skin beco mes scarlet and painful, which quickly spreads to other areas. Flaky areas appear scalded. The wear of the barrier protection that the skin has can cause sepsis and hydroelectrolytic imbalances. The diagnosis is based on clinical suspicion, although confir a biopsy. mation usually requires Biopsy samples show the appearance of a superficial detachment in the noninflammatory epidermis. The treatment consists of the administration of antibiotics according to their weight and the severity of the skin lesions.